Nāmahʹhā-yi dastnivīs-i Jāmī - Jāmī, 1414-1492 (Akādimī-i ʻUlūm-i J. D. A., Markaz-i Zabānhā va Adabīyāt, Dīpārtmint-i Zabān va Adabiyāt-i Darī, 1985)
Letters of classical Persian poet and mystic, written to his contemporary Mīr ʻAlī Shīr Navāyī on various social topics.